2021
DOI: 10.1038/s41598-021-95238-6
|View full text |Cite
|
Sign up to set email alerts
|

White matter tract-specific alterations in patients with primary restless legs syndrome

Abstract: Prior diffusion tensor imaging (DTI) studies have investigated white matter (WM) changes in patients with primary restless legs syndrome (RLS), but the results were inconsistent. Here, we proposed using tract-specific statistical analysis (TSSA) to find alterations in specific WM tracts to clarify the pathophysiological mechanisms of RLS. We enrolled 30 patients with RLS and 31 age- and sex- matched controls who underwent brain magnetic resonance imaging, neuropsychological tests, and polysomnography. Fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…In addition, no studies eligible for inclusion were found by searching the reference list for potentially relevant studies. Finally, we determined that 27 studies existed that met the inclusion criteria, 26 of which were included in the meta-analysis ( 13 , 24 49 ). Since one of the studies had a score of <7 on the NOS, it was excluded ( 50 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, no studies eligible for inclusion were found by searching the reference list for potentially relevant studies. Finally, we determined that 27 studies existed that met the inclusion criteria, 26 of which were included in the meta-analysis ( 13 , 24 49 ). Since one of the studies had a score of <7 on the NOS, it was excluded ( 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…For the diagnosis of RLS, PSG gives objective evidence ( 10 , 12 ). A previous imaging investigation had demonstrated that there was a negative correlation between the fractional anisotropy (FA) values in the left corticospinal tract and the number of movement arousal index (MAI) in patients with RLS, implying clinical significance ( 13 ). Although previous studies have attempted to investigate changes in the nighttime features of patients with RLS, there may be heterogeneity between studies involving clinical variables (such as disease duration, medication status, and disease type), demographic characteristics (such as sex and age), and research methods (such as PSG scoring methods and adaptation nights), so the exact differences in sleep features between healthy controls (HCs) and patients with RLS have not been fully established.…”
Section: Introductionmentioning
confidence: 99%
“…As myelin synthesis depends on iron, myelin deficit in RLS could be reflected in white matter changes. Of note, a recent study reported a correlation between fractional anisotropy (FA) values in the right anterior thalamic radiation and anxiety levels, as well as between FA values in the left corticospinal tract and the number of PLM and the movement arousal index, thus linking structural changes to clinical parameters (Park et al, 2021).…”
Section: Neuroimagingmentioning
confidence: 99%
“…Regarding MRI structural changes, there is a lack of consistency in grey matter findings (Mogavero et al, 2021; Park, Kim, Oh, Seong, & Joo, 2021; Rizzo et al, 2017; Sheng et al, 2021) whereas more consistent white matter changes in the sensory‐motor and limbic/nociceptive networks have been reported (de Paiva et al, 2020; Lee et al, 2018; Park et al, 2021; Rizzo et al, 2017; Stefani et al, 2019). As myelin synthesis depends on iron, myelin deficit in RLS could be reflected in white matter changes.…”
Section: Neuroimagingmentioning
confidence: 99%
“…Compared to the commonly used tract-based spatial statistics method, TSSA is not affected by intersubject variability and more accurately evaluates tract-specific diffusion coefficients. Using the TSSA method, altered WM integrity in patients with subcortical vascular cognitive impairment ( Jung et al, 2016 ), narcolepsy ( Park et al, 2020 ), obstructive sleep apnea ( Koo et al, 2020 ), and restless legs syndrome ( Park et al, 2021 ) has been reported.…”
Section: Introductionmentioning
confidence: 99%